Reconsidering the "Place" in Field Placement. Issue 5 (September 2022) - Fifolt, Matthew; McCormick, Lisa C.; Zhong, Deanna; Lloyd, Laura M.; Alperin, Melissa
Site-based, in-person field placement experiences prepare students for real-world community practice through reflection; direct, hands-on experience; and the completion of a project or set of deliverables that add value to the organization. These practice experiences encourage students to integrate classroom learning with the knowledge and skills of a workplace environment. In the Southeast United States, the Region IV Public Health Training Center (R-IV PHTC) provides students with practice experiences through the Pathways to Practice Scholars Field Placement Program. Before COVID-19, these field placement experiences were limited to in-person assignments in which students worked and lived in the communities they served. However, student and mentor experiences during the COVID-19 pandemic demonstrated that remote work arrangements offer a viable alternative to the onsite-only field placement experience. In this article, we describe student experiences with remote and hybrid work arrangements, highlight issues regarding equity and inclusion, and discuss implications for future public health practice.